Zero liquid discharge and water conservation through water reclamation & reuse of biotreated palm oil mill effluent: A review - Jami, Mohammed Saedi; Amosa, M. K.; Muyibi, Suleyman Aremu; Al-Khatib, Ma'an Fahmi Rashid; Jimat, Dzun Noraini (Progress Publishing Company, 2013)
World natural resources are now going into extinction as evident from the accelerating depletion of our water resources through the persistent but exorable pollutions confronting our water environment daily. Despite this, some part of the world still witnesses overwhelming wastage of fresh water due to lack of proper motivation towards water management policies from the policy makers as well as professionals. Malaysia as a country was known as a place of huge amount of fresh water coupled with regular rainfalls around the year but now witnessing depletion in its fresh waters due to environmental pollution. One of the main causes of this pollution is the palm oil industry which discharges its Biotreated Palm Oil Mill Effluent (BPOME) into the rivers after little but insufficient treatments. This paper reviews the status, rationale and potential of water reuse in Malaysia. The piece further reflects the potential of advanced technologies to produce regenerated water offering specific solutions to industrial or agricultural reuse needs from BPOME, thus suggesting potential, affordable and cost effective water conservation systems through zero liquid discharge (ZLD) technology and water reclamation from BPOME discharge.